1998
DOI: 10.1042/bj3350495
|View full text |Cite
|
Sign up to set email alerts
|

Rapid purification and characterization of l-dopachrome-methyl ester tautomerase (macrophage-migration-inhibitory factor) from Trichinella spiralis, Trichuris muris and Brugia pahangi

Abstract: Macrophage-migration-inhibition factor (MIF) is an essential stimulator of mammalian T-lymphocyte-dependent adaptive immunity, hence MIF orthologues might be expressed by infectious organisms as an immunosubversive stratagem. Since MIF actively catalyses the tautomerization of the methyl ester of l-dopachrome (using dopachrome tautomerase), the occurrence of MIF orthologues in several parasitic helminths was investigated by assaying and characterizing such activity. Evidence of MIF orthologues (dopachrome taut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…In another experiment performed with T. britovi (15000 larvae) on pigs, CPK, AST and ALT presented increased activity during the infection (Oltean et al, 2009). The irrelevant results obtained in the phagocytic assay could be explained through the results obtained by Pennock et al (1998), Tan et al (2001) and Freitas and Pearce (2010), who demonstrated the presence of a macrophage migration-inhibitory factor (MIF) in T. spiralis larvae, very similar to a mammalian cytokine, which might contribute to subversion of host defences. The mammalian MIF is inhibitory for monocyte-macrophage migration, towards glucocorticoid activity (Calandra et al, 1995), immunoglobulin synthesis (Tomura et al, 1999) and natural killer-cell activity (Apte et al, 1998), but not all this properties have been demonstrated yet in MIF produced by T. spiralis.…”
Section: Discussionmentioning
confidence: 84%
“…In another experiment performed with T. britovi (15000 larvae) on pigs, CPK, AST and ALT presented increased activity during the infection (Oltean et al, 2009). The irrelevant results obtained in the phagocytic assay could be explained through the results obtained by Pennock et al (1998), Tan et al (2001) and Freitas and Pearce (2010), who demonstrated the presence of a macrophage migration-inhibitory factor (MIF) in T. spiralis larvae, very similar to a mammalian cytokine, which might contribute to subversion of host defences. The mammalian MIF is inhibitory for monocyte-macrophage migration, towards glucocorticoid activity (Calandra et al, 1995), immunoglobulin synthesis (Tomura et al, 1999) and natural killer-cell activity (Apte et al, 1998), but not all this properties have been demonstrated yet in MIF produced by T. spiralis.…”
Section: Discussionmentioning
confidence: 84%
“…In other studies on parasites, the existence of host cytokine-like molecules, such as homologs of migration inhibition factor in Burgia malayi (Pastrana et al 1998;Pennock et al 1998), IFN-c-like protein in Trichuris muris (Grencis and Entwistle 1997) and IL-4-like molecules in Anisakis simplex (Cuellar et al 2001) have been reported. In western blot analysis, however, we could not find generally recognized sizes of molecules.…”
Section: Discussionmentioning
confidence: 95%
“…Our data strongly suggest that macrophages provide a crucial link between parasitic infections and eosinophil chemotaxis. Because the production of MIF-like enzymatic activity has been demonstrated in a variety of nematode parasites (35), Ym1 induction by parasite-secreted MIF and subsequent eosinophil recruitment to the tissues could be a widely spread mechanism accounting at least partially for the well-known phenomenon of tissue eosinophilia in parasitic infections. Although each of these events has been demonstrated in isolation, we have not yet shown a direct link between BmMIF, YM1 induction, and recruitment of eosinophils.…”
Section: Discussionmentioning
confidence: 99%